Student Involvement In Implementing Homevisit Tutoring - Mafaza, Arida Zumrotul Nur; Wahyuni, Sri; Listyaningrum, Anggia (Proceedings Series of Educational Studies, 2024)
Private tutoring is teaching given face-to-face or in small groups outside an official educational environment such as a school. Private tutoring is a preferred method for students to seek further help in a particular subject or to improve their understanding in a particular area. For students who prefer a more focused learning environment or have difficulty understanding academic content, private tutoring is often an option. This research uses a qualitative method with a phenomenological type. The location of this research is the Dynamic Tutoring Institute, Jl. Imam Sujono No. 30, Sukun, Malang City. The data collection techniques used in this research were observation, interviews and documentation studies. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. To check the validity of the data, researchers used source and time triangulation. The research results show the criteria that a tutor must have in terms of achievement, character and professionalism. Apart from that, this research also discusses student involvement in implementing tutoring activities. Based on the data obtained, various kinds of activities can be carried out by students involved in implementing home visit tutoring. Keywords: Homevisit Tutoring, Student Involvement in Tutoring, Strategies to Increase Enthusiasm